Biodegradation Study of Polymer Composites Reinforced by Areca catechu fibers (Areca catechu L.) and Snake plant fibers (Sansevieria Trifasciata) - Tasya Natalia Lumban Gaol; Nurfajriani Nurfajriani (Universitas Negeri Medan, 2023)
Natural fiber components are used for composite materials because they provide strength to the fibers. Composite materials commonly used are thermoset polymers, one of which is epoxy resin. Biodegradation aims to determine the rate of change in the mass of the specimen after 40 days of burial. The purpose of this study was to determine the effect of the volume fraction of the combination of areca catechu fibers and snake plant fibers on biodegradation properties. The method used in this research is the soil burial test, which is to determine the rate of polymer biodegradation in the soil. The best results in the biodegradation property test obtained the highest mass value of 30% variation obtained after burial for 40 days amounting to 13,417 grams, with the biodegradation test obtained a comparison before and after burial the mass value obtained did not experience a significant increase, this is because the composite material have no pores. or holes for the entry of microorganisms into the soil.